Reliable heuristic mapping method for survivable virtual network - Qiang ZHU; Hui-qiang WANG; Chun-guang MA; Guang-sheng FENG; Hong-wu LV (Tongxin xuebao, 2015)
For reliable virtual network mapping problem,virtual network survivability constraints are introduced to ensure that the rest of the mapped virtual network remains connected under a single node failure condition in the substrate network,which makes sure the completeness of the virtual network and continuity of services.In order to reduce cost of the substrate network,the reliable heuristic mapping problem is considered as an integer linear programming model and a reliable heuristic mapping method for survivable virtual network is proposed to solve the problem.The simulation results show that average usage of links is reduced and the success rate,average revenue of mapping,recovery success rate of virtual network are increased compared with the existing reliable mapping algorithms.